2018
DOI: 10.3897/mycokeys.29.21122
|View full text |Cite
|
Sign up to set email alerts
|

Curvularia microspora sp. nov. associated with leaf diseases of Hippeastrum striatum in China

Abstract: An undescribed Curvularia sp. was isolated from the leaf spot disease of Barbados Lily (Hippeastrum striatum (Lam.) Moore). Phylogenetic analyses of combined ITS, 28S, GPD1 and TEF1 sequence data place nine strains of this species in the trifolii-clade, but they clustered together as an independent lineage with strong support. This species was morphologically compared with related species in the trifolii-clade. Based on differences in morphology and phylogeny, it is concluded that this species is a new taxon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Our phylogenetic tree, based on 54 reported ITS sequence data of Curvularia diseases in these countries (Figure 2), also indicated that this approach is not effective for identifying these pathogens, especially in the case of C. lunata as a prevalent species. However, identification of Curvularia isolates by multi-gene phylogenetic analyses has withstood scrutiny (Liang et al 2018;Wang et al 2018;Zhang et al 2018). Additionally, nearly all reports, even for severe diseases, are based on a single isolate, which preclude an objective evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our phylogenetic tree, based on 54 reported ITS sequence data of Curvularia diseases in these countries (Figure 2), also indicated that this approach is not effective for identifying these pathogens, especially in the case of C. lunata as a prevalent species. However, identification of Curvularia isolates by multi-gene phylogenetic analyses has withstood scrutiny (Liang et al 2018;Wang et al 2018;Zhang et al 2018). Additionally, nearly all reports, even for severe diseases, are based on a single isolate, which preclude an objective evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…BIOMIGA, Inc., San Diego, California, USA) was used to extract the genomic DNA. DNA amplification was performed in a 25 μl reaction volume which contained 2.5 μl 10 × PCR buffer, 1 μl of each primer (10 μM), 1 μl template DNA, 0.25 μl Taq DNA polymerase (Promega, Madison, WI, USA) and 18.5 μl ddH 2 O. Primers used and thermal cycling programme for PCR amplification of the ITS (ITS4/ITS5), GAPDH (gpd1/gpd2) and tef1 (EF-526F/1567R) genes were followed as described previously (White et al 1990;Berbee et al 1999;Schoch et al 2009;Liang et al 2018).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…For example, there are 39 introns in the Pezizomycotina subphylum mitogenome and two in the Fusarium oxysporum mitogenome [44]. Moreover, 1,5,5,13,15,18,33,35,38 introns were identified in S. bambusicola, B. maydis, P. nodorum, S. lycopersici, Didymella pinodes, P.tritici-repentis, B. cookie, Leptosphaeria biglobosa, Leptosphaeria maculans, respectively. However, we did not identify any introns within the M. graminicola mitogenome, which was consistent with a previous study [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also described the presence of L. chartarum conidia in indoor air environments where asthma patients reside [14,15]. C. trifolii, a widely distributed, high-temperature pathogen, causing leaf spot on Trifolium alexandrinum (Berseem clover) and leaf blight on Agrostis palustris (creeping bentgrass) [16][17][18]. Moreover, C. trifolii can produce various secondary metabolites in culture, among which, some exhibited excellent anti-inflammatory and antitumor activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted using Fungus Genomic DNA Extraction Kit (Biomiga #GD2416, San Diego, California, USA) and following the manufacturer's instructions. PCR amplification of the internal transcribed spacer (ITS) region and the large subunit (LSU) of the ribosomal RNA gene was performed in a 25-μl reaction volume system as in Liang et al (2018) . Primers V9G and ITS4 ( White et al 1990 , de Hoog and van den Ende 1998 ) were used to amplify the ITS and LSU1Fd and LR5 for the LSU ( Vilgalys and Hester 1990 , Crous et al 2009 ).…”
Section: Methodsmentioning
confidence: 99%